Demograficzne implikacje pandemii COVID-19 : perspektywa zdrowia publicznego - Szymborski, Janusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The aim of the study is to try to assess the impact of the COVID-19 pandemic on four main segments of Poland’s population policy: family policy aimed at creating conditions conducive to the implementation of reproductive plans; senior policy, migration policy and health policy aimed at improving the health of the population and reducing mortality. It has been shown that the pandemic has a detrimental effect on the deepening of already adversely developing demographic processes in Poland. First of all, there was a dramatic increase in mortality and negative population growth on an unprecedented scale. The phenomena that constitute a significant obstacle in the fight against pandemics (infodemia) and those whose consideration may help in understanding the specificity of the course of infection and help reduce its health, social and demographic consequences (syndemia) are also discussed. There are many indications that the unfavorable development of the third wave of the pandemic in Poland, as well as in other countries of Central and Eastern Europe, is due to, on the one hand, the unsatisfactory health condition of the population, and on the other hand, it results from deficiencies in the functioning of the health care system. An open list of several dozen research topics has been proposed, which may contribute to updating the goals and directions of the population policy in Poland. In the context of demographic changes, the reasons for the debate on the redefinition of the approach to public health in the Polish health care system were discussed, with an emphasis on health education, legislation and social care.
Keywords: COVID-19 pandemic; demography; excess mortality; health care system